A proposed guidance program for the grade school students of St. Paul College of Manila - Batto, Ma. Antonina Laguatan (Animo Repository, 1971)
v. 1. This study proposes a guidance program to coordinate the existing guidance services in the grade school department of St. Paul College of Manila. The deliberative approach, in which data were gathered from interviews, observations, guidance records, and manuals, was used in this study. Readings of related studies and researches on elementary school guidance supplemented the approach in presenting the theoretical construct of a proposed guidance program in the grade school department of St. Paul College of Manila. In the grade school, the on-going services were Individual Inventory, Counseling, and Testing and Research. Three other services were proposed to meet the needs of the students which consisted of the following : Placement, Follow-up and Information. Proposed procedures for the implementation of these services were discussed. Implementation of the services was deemed feasible through the different activities proposed and with the cooperation of the administration, faculty, parents, and students. Awareness of the existing program and knowledge of the roles each one played in making the program effective could be disseminated through the information service, which would provide activities such as orientation programs, in-service training programs and meetings with parents. It was recommended that adequate and enthusiastic support be given by the administration and faculty for the implementation of the guidance program. In-service training for faculty members should be held at least monthly or once in two months. An orientation program should also be planned for kindergarten pupils, grade seven pupils, and new students. It was recommended that a general meeting with parents at the start of the school year to introduce the guidance program in the grade school be held. Guidance brochures could also be distributed to faculty members, students, and parents. It was suggested that regular meetings be held between guidance counselors, faculty, parents and the principal. Adequate budget should be provided